Assessment of dexterity and diagnostic accuracy of the Functional Dexterity Test in patients with carpal tunnel syndrome - Sartorio, Francesco; Vercelli, Stefano; Bravini, Elisabetta; Zanetta, Anna; Bargeri, Serena; Pisano, Fabrizio; Ferriero, Giorgio (La Medicina del Lavoro, 2018)
Background: The diagnosis of carpal tunnel syndrome (STC) is centered on the symptoms. However, patients also show an impairment of sensorimotor functions, but the relationship between STC and manual dexterity has never been investigated. Objectives: To analyze the correlation between manual dexterity and severity of the STC. Another objective was the diagnostic accuracy of the clinical battery including provocative tests (Phalen, Tinel) and Functional Dexterity Test (FDT). Methods: A sample of 80 subjects with suspected STC was subdivided into 4 groups based on EMG (severe/extreme-GrA, moderate-GrB, mild/minimal-GrC, negative-GrD) and evaluated in blind by Phalen, Tinel and FDT. The relationship between the FDT and the allocation of subjects was investigated by Spearman’s rho, while the groups were compared with univariate ANOVA and Tukey’s post hoc analysis. Diagnostic accuracy of the clinical battery was expressed by sensitivity, specificity, and likelihood ratios (LR). Results: A moderate (r=0.48, p<0.001) correlation was found between FDT and the 4 groups. ANOVA has returned a significant difference between GrA vs. all others and between GrB vs. GrD. The battery showed a sensitivity, specificity, positive likelihood ratio (LR+) and negative likelihood ratio (LR-) of 70%, 94%, 11.98 and 0.31 respectively. Conclusions: The results of this study supported the hypothesis that STC patients also have a dexterity impairment. The FDT was able to discriminate between three levels of severity (negative, mild to moderate, severe to extreme), maintaining a good level of diagnostic accuracy in addition to provocative tests.